In Search for Islamic Macroprudential Policy in Indonesia: The Case of Financing to Value (FTV) and Property Financing - Qoyum, Abdul; Fauziyyah, Neneng Ela (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2018)
This study aims to examine the impact of macroprudential policy particlarly the relaxing of Financing to Value (FTV) on property financing of Islamic bank in case of Indonesia. In addition, this paper also analyzes the impact of macroeconomic variables and specific factors on property financing in Islamic Bank. This paper collects data from the Bank Indonesia website, the Financial Services Authority (FSA) and the Central Statistics Agency (CSA) form January 2010 until April 2016. By employing Vector Error Correction Model (VECM), this study found that inflation and Industry Produce Index (IPI) have been positively influence on the property financing, while the BI rate and financing to deposit ratio (FDR) have been negatively influence on the property financing. While the relaxing of FTV policy also negatively influence on the property financing. Therefore, This study conludes that the policy have not effectived yet.